2019
DOI: 10.5688/ajpe7196
|View full text |Cite
|
Sign up to set email alerts
|

A Job Analysis to Define the Role of the Pharmacy Preceptor

Abstract: Objective. To use a comprehensive job analysis to identify and describe the roles and responsibilities of pharmacist preceptors. Methods. After gathering input from local pharmacist preceptors, a task inventory questionnaire was created that included 92 tasks divided among nine domains related to the job of preceptors. The task inventory questionnaire was distributed to expert pharmacist preceptors in the United States, which were those who had been recognized for excellence in precepting by a national organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…As an educator, preceptors should supplement knowledge learnt in the classroom and facilitate the application of theory to the practice. For this purpose, preceptors should be orientated to the university curriculum and be confident in using effective teaching strategies to encourage students to reflect, think critically and problem solve (DeAngelis & Wolcott, 2019;Enderby et al, 2021;O'Sullivan et al, 2020). Familiarity with the pharmacy curriculum was rated lower in importance for preceptors in this study, which may be related to the high proportion of preceptors (47.3%) having studied at JCU and therefore already having a good knowledge of how the course is structured.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…As an educator, preceptors should supplement knowledge learnt in the classroom and facilitate the application of theory to the practice. For this purpose, preceptors should be orientated to the university curriculum and be confident in using effective teaching strategies to encourage students to reflect, think critically and problem solve (DeAngelis & Wolcott, 2019;Enderby et al, 2021;O'Sullivan et al, 2020). Familiarity with the pharmacy curriculum was rated lower in importance for preceptors in this study, which may be related to the high proportion of preceptors (47.3%) having studied at JCU and therefore already having a good knowledge of how the course is structured.…”
Section: Discussionmentioning
confidence: 78%
“…As an assessor, the preceptor is required to examine the performance of the student in the practice. A critical component of being an assessor is the provision of feedback, which enables the student to monitor their progress toward meeting their performance criteria (DeAngelis & Wolcott, 2019;Knott, Mylrea & Glass, 2020). This study suggested that preceptors should provide unbiased student assessment and feedback that is timely and constructive.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…DeAngelis and Wolcott described a preceptor model, in which three critical tasks were provided to the pharmacy interns by the preceptors in the training setting. These tasks are related to professionalism in stressful situations, commitment to service, and ethical and moral decision-making [ 25 ].…”
Section: Inpatient Settingmentioning
confidence: 99%
“…Although no nursing preceptor practice analysis has been found, DeAngelis and Wolcott (2019) conducted a job analysis to determine the roles and responsibilities of pharmacist preceptors. A task inventory survey was developed from feedback from pharmacy preceptors and consisted of 92 tasks, representing nine practice domains: planning/logistics, intrapersonal, interpersonal, clinical knowledge, assessment, leadership, professionalism, teaching, and communication.…”
Section: Introductionmentioning
confidence: 99%